Assessment of the efficacy of different herbicides on growth parameters of Fenugreek in Western Rajasthan - Vikash Meena; M. L. Mehriya; Anuj Kumar; P.R. Raiger (Annals of Agricultural Research, 2024)
The field experiment entitled “Efficacy of Herbicides in Fenugreek (Trigonella foenum-graecum L.)” was conducted at experimental field of the Agricultural Research Station Mandor, Jodhpur during Rabi season of 2021-22. The treatments consisting of ten treatments of herbicides viz. Pendimethalin 1 kg/ha, PE (T1), Pendimethalin + Imazethapyr (Ready mix) 800 g/ha, PE (T2), Diclosulam 20 g/ha, PE (T3), Flumioxazin 100 g/ ha, PE (T4), Imazethapyr 50 g/ha (20 DAS) (T5), Sodium aciflurofan + Clodinafop propargyl (Ready mix) 210 g/ha (20 DAS) (T6), Fomesafen + Fluazifop p-butyl 220 g/ha 20 DAS (Ready mix) (T7), Fluazifop p-butyl, 250 g/ha (20 DAS) (T8), weed free (T9) and weedy check (T10)were laid out in randomized block design with three replications. It was found that application of Pendimethalin + imazethapyr (Ready mix) 800 g/ha, PE recorded significantly higher growth attributes such as plant height (48.41 cm), total no. of branches plant-1 (4.95) and dry matter accumulation plant-1(16.70 g) at harvest. Among herbicides, Pendimethalin 1 kg/ha, PE, Imazethapyr 50 g/ha, (20 DAS), Fluazifop p-butyl, 250 g/ha, (20 DAS), Flumioxazin 100 g/ha, PE and Diclosulam 20 g/ha, PE were found statistically equally effective in controlling weeds in fenugreek.q